Influence of context-specific cognitions and values on pro-environmental land management in the Rio Savegre watershed, Costa Rica - Espinoza Cisneros, Edgar (2020)
Unsustainable land use practices pose significant global environmental challenges. While land use decision-making has been examined from various analytical approaches in research, relatively little attention has been given to the role that cognitive factors (values, beliefs, etc.) play in land management decisions in various sociopolitical, economic and biophysical contexts. In this paper, the influence that certain context-specific cognitions and relational values linked to fluvial systems have on the adoption of pro-environmental land use practices is examined in a watershed in Costa Rica, recently designated part of a UNESCO Biosphere Reserve for its exceptional biological diversity and sociocultural importance. Results indicate that, within this watershed, reported effects of knowing about environmental narratives, perceptions of fluvial system threats, and age, were significantly associated with higher levels of adoption of pro-environmental land use practices minimizing negative impacts on the fluvial system. These results highlight the role that environmental narratives might play in galvanizing pro-environmental management in rural contexts in Latin America, as well as how more effective land management strategies can be designed and implemented by considering context-specific cognitions and values of land managers.